2013
DOI: 10.1583/12-4175.1
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fenestration of Aortic Stent-Grafts: Implications of Puncture Methods for in Situ Fenestration Durability

Abstract: Different endografts behave significantly differently when fenestrations are fashioned. Optimum puncture/dilation is important when considering in vivo fenestration techniques. Improvements in instrumentation, materials, and techniques are required to make this a reliable and reproducible endovascular option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 24 publications
0
49
0
Order By: Relevance
“…A type I arch anatomy exhibits a better approach with a laser fiber located perpendicularly to the graft. This arch decreases the chance that the laser fiber will slip forward proximally from the graft to the aortic arch . According to Riga et al, the quality of in situ fenestrations correlated with a more perpendicular approach .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A type I arch anatomy exhibits a better approach with a laser fiber located perpendicularly to the graft. This arch decreases the chance that the laser fiber will slip forward proximally from the graft to the aortic arch . According to Riga et al, the quality of in situ fenestrations correlated with a more perpendicular approach .…”
Section: Discussionmentioning
confidence: 99%
“…This arch decreases the chance that the laser fiber will slip forward proximally from the graft to the aortic arch . According to Riga et al, the quality of in situ fenestrations correlated with a more perpendicular approach . Redlinger et al noted that a type III arch should be better deployed with a chimney graft .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Saari et al 13 characterized the acute changes with various combinations of devices. Most recently, Riga et al 14 have investigated the effects of the puncture angle during in situ fenestration on various devices, in addition to the use of cutting balloons. This has added much more insight into the technique of in situ fenestration.…”
Section: Discussionmentioning
confidence: 99%
“…Bench examination of the fenestration under various circumstances revealed that fenestrations of the graft with an acute angle between the fabric and the needle tend to create a non-circular hole or tear on the fringe of the fenestration [7,8], which compromises the quality of fenestration and can potentially lead to type III endoleaks or tear Fig. 2 A Schematic drawing of the squid-capture technique for in situ fenestration.…”
Section: Discussionmentioning
confidence: 99%